Straw–Brick‐Like Carbon Fiber Cloth/Lithium Composite Electrode as an Advanced Lithium Metal Anode. Issue 8 (30th April 2018) - Liu, Sufu; Xia, Xinhui; Yao, Zhujun; Wu, Jianbo; Zhang, Liyuan; Deng, Shengjue; Zhou, Chengao; Shen, Shenghui; Wang, Xiuli; Tu, Jiangping
Abstract: Because of its highest capacity and lowest anode potential, lithium (Li) metal anode is extremely attractive to the next‐generation rechargeable batteries. However, low Coulombic efficiency, uncontrolled dendritic growth, and poor solid electrolyte interphase (SEI) during the Li stripping/plating process hinder its practical application. Here, a novel straw–brick‐like carbon fiber cloth/lithium (CFC/Li) composite electrode is designed by embedding lithium into 3D carbon cloth matrix via a facile ZnO‐induced molten method. The ZnO layer on the CFC provides bonding interactions for encapsulation of molten Li metal to form straw–brick‐like CFC/Li composite electrode. Compared with bare Li metal electrode, the as‐obtained CFC/Li electrode presents much less fluctuant stripping/plating profiles with lower voltage hysteresis (120 mV at 3 mA cm −2 ) and more stable SEI structure. When coupled with a LiFePO4 cathode, the CFC/Li anode demonstrates a good suitability in full cells. This reinforcement is due to the unique straw–brick‐like structure with good conductive framework leading to greatly decreased current density, and effective suppression of volume change and dendrite. This modification strategy on the Li metal provides an easy straightforward option for construction of advanced anodes for Li‐metal batteries. Abstract : A unique straw–brick‐like Li metal composite anode is constructed through rational combination of carbon fiber cloth (CFC) and Li metal. The CFC/Li composite anode exhibits good flexibility and great potential for large‐scale production. Attributed to ultralow current density, stabilized solid electrolyte interface (SEI) film, and limited volume change, the CFC/Li anode exhibits lower hysteresis, enhanced cycling stability, and effective dendrite suppression.